2022
DOI: 10.1038/s41598-022-17265-1
|View full text |Cite
|
Sign up to set email alerts
|

Gastruloids as in vitro models of embryonic blood development with spatial and temporal resolution

Abstract: Gastruloids are three-dimensional embryonic organoids that reproduce key features of early mammalian development in vitro with unique scalability, accessibility, and spatiotemporal similarity to real embryos. Recently, we adapted the gastruloid culture conditions to promote cardiovascular development. In this work, we extended these conditions to capture features of embryonic blood development through a combination of immunophenotyping, detailed transcriptomics analysis, and identification of blood stem/progen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 71 publications
1
11
0
Order By: Relevance
“…Our hemogenic gastruloid system extends recent findings by (Rossi et al, 2022), who observed early erythro-myeloid specification in a gastruloid protocol previously developed for modelling of primordial heart development (Rossi et al, 2021). Together, our data highlight the power of gastruloid models in faithfully capturing mid-development specification of lateral mesoderm-derived programs.…”
Section: Discussionsupporting
confidence: 83%
“…Our hemogenic gastruloid system extends recent findings by (Rossi et al, 2022), who observed early erythro-myeloid specification in a gastruloid protocol previously developed for modelling of primordial heart development (Rossi et al, 2021). Together, our data highlight the power of gastruloid models in faithfully capturing mid-development specification of lateral mesoderm-derived programs.…”
Section: Discussionsupporting
confidence: 83%
“…Although these organoids closely recapitulate patterns of early cardiogenesis, one major limitation of this model is the formation of mid/hindgut tissue, as identified by expression of the marker CDX2, instead of foregut endoderm as in native heart development. A follow-up study captured features of embryonic blood development in these gastruloids, increasing the complexity and value of this multi-tissue model ( Rossi et al, 2022 ). Olmsted and Paluh applied the protocol from Rossi et al (2021) to their human gastruloids, achieving a combined model for cardiogenesis, foregut development and neurogenesis ( Olmsted and Paluh, 2022 ).…”
Section: Cardiac Organoidsmentioning
confidence: 99%
“…Variations of gastruloid culture conditions bias the system towards different outputs [ 75–82 ] and are discussed elsewhere in this issue. For the purpose of this review, we will consider recent reports describing the blood generation potential of gastruloids [ 76 , 77 ], summarised in Figure 2 . We will also review information on the specification of mesodermal lineages, as these are critical first events on the generation of endothelium and blood.…”
Section: Gastruloid Models Of Blood Formationmentioning
confidence: 99%
“… Black timeline represents the starting point of each protocol, up until the termination. ( A ) Protocol used by Rossi et al [ 76 ], where 300–700 cells were aggregated into 96 well-round bottom plates cultured in N2B27. A pulse of CHI99021 was added between 48 and 72 h. Post-96 h, the aggregates were transferred into 24-well plates shaking on orbital shaker (as shown in grey box) and cultured in N2B27, VEGF, bFGF and AA until 14 4h.…”
Section: Gastruloid Models Of Blood Formationmentioning
confidence: 99%